The Importance of consumer behavior: ifferentiating factor of organizations (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
The aim of this paper is to reflect on the behavior of consumers and their relative importance in the consumption of products and services. Companies must devise a simple but effective feedback system that allows them to know every day the wishes of their clients, who can know with any degree of accuracy, move to where the interests, desires and tastes of their buyers and upgrade their inventories and the best way to offer. Also need to stay informed about the movements of the competition, management of prices and the kind of publicity that these forward. Every day there are more options on the market, and of course, greater competition. Successful organizations today, perceive the impact and significance of the consumer in their present and future and its market share. The consumer is regarded as the king, because in a way companies have to meet their needs in a process of constant adaptation, through which experts distinguish these needs and define strategies that are to satisfy. Consumers are changing their preferences and priorities, so the companies that respond to this change will succeed. Therefore, in-depth study and analysis is a relevant tool to differentiate themselves from competitors and better meet consumer tastes.
Keywords: consumers; culture; marketing; image; symbols